Swadeshi Reimagined: The Case for Indian Homoeopathy as a National Healthcare Asset (Homoeopathy for All, 2026)
In today’s interconnected world, the  meaning of Swadeshi must evolve  beyond its narrow interpretation  of geographical origin. In its true  contemporary sense, Swadeshi is  not merely about where an idea was  born—it is about where it has taken  root, where it has grown, and whom  it serves. Swadeshi, today, must be defined  by: • Value creation within the nation • Indigenous capacity-building • Contribution to public welfare • Integration into national systems • Acceptance by the people By this evolved definition, India  has already embraced a pragmatic  Swadeshi philosophy in multiple  sectors.
Keywords: geographical origin; national economy; epicentre of Homoeopathy